ANALISIS PENOLAKAN KREDIT INVESTASI ATAS PEMBELIAN SATU UNIT BREAKBULK CARRIER OLEH PT ABC DI BANK BII - , Affan Ghiffari, S. E, Dr. Erni Ekawati, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PT ABC is a national shipping company where located in Jakarta had proposed an investment credit to Bank International Indonesia (BII) in the first semester of 2008. The company had planned to buy 1 (one) unit of breakbulk carrier with value USD17.000.000, + 10.500 DWT which built less than 10 years. The ship will be used for PT Aneka Tambang which carried for Ferronickel cargo from Pomala (Sout East Sulawesi) to Rotterdam. The Proposal had already proposed by Business Unit to Loan Committee in BII. The entire document in the proposal had already complied with the terms and condition of credit proposal standard in BII. We, as BU already analyzed with all credit tools in BII standard such as 5Câs, Cash Flow Analysis, Financial Ratio, Risk Mitigation and also a potential risk is already proposed and explained well in the credit proposal by BU. The member of LC in the head quarter of BII, from Risk Manager to Chief Credit Officer had review and analyzes the proposal, meanwhile when the proposal came to the Risk Director